2016
DOI: 10.7554/elife.17361
|View full text |Cite
|
Sign up to set email alerts
|

Satb2 determines miRNA expression and long-term memory in the adult central nervous system

Abstract: SATB2 is a risk locus for schizophrenia and encodes a DNA-binding protein that regulates higher-order chromatin configuration. In the adult brain Satb2 is almost exclusively expressed in pyramidal neurons of two brain regions important for memory formation, the cerebral cortex and the CA1-hippocampal field. Here we show that Satb2 is required for key hippocampal functions since deletion of Satb2 from the adult mouse forebrain prevents the stabilization of synaptic long-term potentiation and markedly impairs lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 85 publications
(100 reference statements)
3
78
0
Order By: Relevance
“…SAS is a multi‐system disorder caused by alterations of the SATB2 gene, a transcription factor that binds to nuclear matrix‐attachment regions (MARs) and activates the transcription of genes that are critical to the development of multiple organ systems, tissues, including the jaw, brain, and skeleton (Britanova et al, ; Dobreva et al, ; Dobreva, Dambacher, & Grosschedl, ; Gyorgy, Szemes, de Juan Romero, Tarabykin, & Agoston, ; Jaitner et al, ). In this manuscript we provide the basis to better characterize the natural history and assess genotype‐phenotype correlations.…”
Section: Discussionmentioning
confidence: 99%
“…SAS is a multi‐system disorder caused by alterations of the SATB2 gene, a transcription factor that binds to nuclear matrix‐attachment regions (MARs) and activates the transcription of genes that are critical to the development of multiple organ systems, tissues, including the jaw, brain, and skeleton (Britanova et al, ; Dobreva et al, ; Dobreva, Dambacher, & Grosschedl, ; Gyorgy, Szemes, de Juan Romero, Tarabykin, & Agoston, ; Jaitner et al, ). In this manuscript we provide the basis to better characterize the natural history and assess genotype‐phenotype correlations.…”
Section: Discussionmentioning
confidence: 99%
“…While postnatally, Satb2 is required for proper dendritic and soma adhesion of callosal neurons in neocortex [32]. In adult, Satb2 deletion leads to impairment in long-term memory [33,34]. We also reported that mice with loss of Satb2 in cortex and hippocampus show hyperactivity, increased impulsivity, abnormal social novelty, and impaired spatial learning and memory [35].…”
Section: Introductionmentioning
confidence: 80%
“…Recently, we found that emotional behavior and spatial learning and memory were impaired in Satb2 CKO mice [35]. Rsp-or CA1-specific Cre is needed to exclusively delete Satb2 for elucidating its function in these regions, which will promote our understanding of how Satb2 is involved in neurodevelopmental diseases and psychiatric disorders [33].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the highly specific expression pattern of SATB2 in the adult brain and the severe learning disabilities and mental retardation observed in patients diagnosed with SAS (SATB2-associated syndrome), it was hypothesized that SATB2 is critical for human learning and memory [Jaitner et al, 2016]. Interestingly, while SATB2 showed no post-treatment response, its lncRNA, SATB2 antisense, did respond to GnRHa treatment (+1.78 logFC, FDR 0.019).…”
Section: Lower Expression In Hir and No Response To Gnrhamentioning
confidence: 99%
“…Interestingly, while SATB2 showed no post-treatment response, its lncRNA, SATB2 antisense, did respond to GnRHa treatment (+1.78 logFC, FDR 0.019). At the molecular level, BDNF upregulates SATB2 , which itself binds to promoters of coding and noncoding genes [Jaitner et al, 2016]. It was recently shown that the MSI (Musashi) gene induces forgetting and represents a novel mechanism of memory decay by linking translational control to the structure of the neuronal actin cytoskeleton .…”
Section: Lower Expression In Hir and No Response To Gnrhamentioning
confidence: 99%